2017
DOI: 10.15430/jcp.2017.22.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Inflammation by Sucrose Isomer, Turanose, in Raw 264.7 Cells

Abstract: Increased sugar consumption has been proposed to be a risk factor for obesity-related metabolic disorders. The objective of this study was to investigate the anti-inflammatory effect of turanose in Raw 264.7 macrophages. Turanose (3-O-α-D-glucosyl-D-fructose), an isomer of sucrose, naturally exists in honey. For these studies, macrophages were treated with total glucose (Glu), 50% Glu/50% turanose (T50), 25% Glu/75% turanose (T75), and 100% turanose (T100), each with a total concentration of 25 mM in cell medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Turanose is considered to be a suitable sucrose replacement for patients with metabolic symptoms or disorders, because it is digested more slowly than sucrose with crude hog intestinal digesta preparation (Dahlqvist 1960) and with rat intestinal enzyme mixture (Hodoniczky et al, 2012). In addition, turanose displayed anti-obesity effects in vitro by inhibitory function on lipid accumulation, and the down-regulated lipopolysaccharide-and glucose-induced inflammation through inflammatory cytokine modulation in the Raw 264.7 macrophages (Chung et al, 2017a;Park et al, 2016).…”
Section: Sucrose Isomer Producing Reactions Of Microbial Assmentioning
confidence: 99%
“…Turanose is considered to be a suitable sucrose replacement for patients with metabolic symptoms or disorders, because it is digested more slowly than sucrose with crude hog intestinal digesta preparation (Dahlqvist 1960) and with rat intestinal enzyme mixture (Hodoniczky et al, 2012). In addition, turanose displayed anti-obesity effects in vitro by inhibitory function on lipid accumulation, and the down-regulated lipopolysaccharide-and glucose-induced inflammation through inflammatory cytokine modulation in the Raw 264.7 macrophages (Chung et al, 2017a;Park et al, 2016).…”
Section: Sucrose Isomer Producing Reactions Of Microbial Assmentioning
confidence: 99%
“…The generation of free oxygen radicals (e.g., NO) is caused by an increase in the levels of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) [ 6 ]. Furthermore, inflammatory factors such as cytokines and bacterial LPS can result in increased iNOS in macrophages, leading to the generation of intracellular ROS [ 7 , 8 ]. Some studies have demonstrated that the overexpression of iNOS or COX-2 may contribute to disease-related inflammation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, inflammatory factors such as cytokines and bacterial LPS can result in increased iNOS in macrophages, leading to the generation of intracellular ROS [ 7 , 8 ]. Some studies have demonstrated that the overexpression of iNOS or COX-2 may contribute to disease-related inflammation [ 8 ]. In inflamed tissue, LPS-activated macrophages play a major role in the production of proinflammatory cytokines, including tumor necrosis factor (TNF)- α , NO, and PGE 2 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the potential use of turanose was reported as a hypoglycaemic sweetener because it is slowly hydrolysed to fructose and glucose compared with sucrose in the intestine (Dahlqvist, 1960). The health functionalities of turanose, such as anti-inflammatory effects, were also carried out (Chung et al, 2017). In addition to the health benefits of turanose, most of the preceding studies have centred on the efficient production of turanose by enhancing its bio-conversion conditions (Park et al, 2016).…”
Section: Introductionmentioning
confidence: 99%